Derivative Analysis of Value Added to Stock Returns at Jakarta Islamic Index - Hasyim, Fuad; Ardityasari, Resyta Aulia (BISNIS, 2020)
This study aims to examine the effect of value added derivative such as economic value added (EVA), market value added (MVA) and refined economic value added (REVA) on stock return with stock price as an intervening variable. The object of this study are all Islamic stocks listed in the Jakarta Islamic Index (JII) in the period 2014-2019. This study using purposive sampling method and obtained by 11 companies. Data processing using panel regression with common, fixed and random modelling approach. The results show that economic value added  (EVA) has no effect either on stock prices or stock returns, market value added (MVA) affects the stock price and stock return, while refined economic value added (REVA) has no effect on both. Then, stock prices are only able to mediate the effect of market value added (MVA) on stock return.